Telling the truth: Don DeLillo in an age of amnesia and redress - Marni Gauthier (Ilha do Desterro)
The December 2006 Iran Holocaust denial Conference and the international excoriation of it reveal a paradox of two cultural strands that are emblematic of the legacy of the twentieth century: official denial and historical amnesia on the one hand; and (inter)national attempts at truth telling and historical redress on the other. Massive violence–and associative denial—punctuate the entire twentieth century. Yet coordinated tenacious efforts at public acknowledgment of “what really happened”–a recurrent and insistent emphasis in this context of trials, reparations, and above all, truth commissions—and concomitant historical redress for state-sanctioned crimes is a particularly recent phenomenon, unique, in fact, to the 1990s. But it is not only political readers who address what Priscilla B. Hayner, in her exhaustive study of truth commissions calls, “unspeakable truths.” This essay addresses the incongruity between the recent global concern with truth telling, official apology, memory and historical redress on the one hand–an obsession that certainly includes the US—and American amnesia on the other. It is in the interstices of these two apposite late twentieth century phenomena–amnesia and truth telling; “history” distinct from “the truth of the past”; “official” opposed to “vernacular” memory — that, I argue, a new genre of historical novel develops and performs a vital cultural work: telling the truth in an age of amnesia and redress. Such novels engage the recalcitrant materials of historical experience to assert truth claims that in turn challenge nationalist histories and revise traditional mythologies. Among the foremost authors of this new “truth-telling” historical novel is Don DeLillo. Americana, the vital precursor to Libra and especially to Underworld, is the definitive harbinger of DeLillo’s third century of work that writes both within and against postmodernism. In these Cold-War era novels, DeLillo ultimately moves beyond the ironized perspective of history that is the distinguishing feature of “historiographic metafiction”; his postmodern narrative techniques (from irony to looping novelistic structures and dense intertextuality) inscribe a critical distance from history only to force a raw encounter with it. As such, DeLillo exploits the tension between innocence and violence–the literally malignant legacy of the Cold War–to reveal the way in which official culture is amnesiac by definition.